A influência da afetividade como mediadora da aprendizagem: um recorte com crianças nos anos iniciais do ensino fundamental - Silva, Eliane Santos da (Universidade Federal do Tocantins, 2022)
Affectivity is one of the most genuine expressions of the human being; from birth to aging. From the first school contact, affection gains notoriety as well as other emotional, cognitive and social skills that are so relevant and demanded in everyday life. In view of this, our research subject/topic arises: Which is the importance of affectivity for an education excellence? The general objective of this study was to look for hypotheses that influence affectivity, based on bibliographic and field research, as a mediator of meaningful learning by children during the early years of Elementary School. The specific objectives sought to explore in the main educational and pedagogical literature, such as those by Wallon, Piaget and Vygotsky, theoretical foundations that supported our initial hypothesis of the connection between affectivity and meaningful learning; aiming to deepen discussion looking for official documents that reveal the importance of affectivity for future generations, enhanced by field research aimed at: (a) understanding the importance of affection; (b) the teacher-student relationship; and, (c) analysis and discussion of field research. The field research was answered by teachers and students by 4th and 5th years at an elementary school at Miranorte municipality in the state of Tocantins, Brazil, whose results, even in the middle of a pandemic, showed a positive an important judgment/standing/position of the affective condition on the learning process, ranking second only behind the importance of a good explanation for the subject being taught.